1998
DOI: 10.1046/j.1365-2540.1998.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genetic variance and isolation by distance in two leaf beetle species: Oreina cacaliae and Oreina speciosissima

Abstract: The distribution of genetic variance was investigated in two closely related Oreina leaf beetle species, Oreina cacaliae and Oreina speciosissima. Populations of these alpine beetles were sampled in mountainous areas of Western Europe, the total sampling area ranging from the Pyrenees to the Czech Republic. Allozyme electrophoresis of 21 (O. cacaliae) and 16 (O. speciosissima) loci revealed high genetic variability as expressed in a high percentage of polymorphic loci (only one monomorphic locus was found in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…We doubt that lack of correlation between geographic distance and call characters was a result of inadequate sampling, as there was a significant IBD effect on the mitochondrial gene. The effect of IBD might have differently influenced call characters and mitochondrial COI sequences in an uncorrelated manner [49], [50]. This conflicting result may also indicate that some selective factors may still be operating on call characters of H. japonica in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…We doubt that lack of correlation between geographic distance and call characters was a result of inadequate sampling, as there was a significant IBD effect on the mitochondrial gene. The effect of IBD might have differently influenced call characters and mitochondrial COI sequences in an uncorrelated manner [49], [50]. This conflicting result may also indicate that some selective factors may still be operating on call characters of H. japonica in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Clear patterns of genetic population structuring due to limited gene flow are common in insects inhabiting high montane regions, or sky islands (Knoll et al . 1996; Knoll & Rowell‐Rahier 1998; Knowles 2001; Mardulyn 2001). Our data additionally show a high level of genetic differentiation between mountain range populations, whereas genetic variability within mountain ranges is low in Drusus discolor .…”
Section: Discussionmentioning
confidence: 99%
“…2005), a feature that might have further limited their dispersal abilities. Molecular‐based analyses on other Oreina species have suggested that populations were generally highly isolated (Knoll & Rowell‐Rahier 1998; Margraf et al. 2007; Borer et al.…”
Section: Introductionmentioning
confidence: 99%